The Impact of Stock Selection, Market Timing and Equity Fund Size on Equity Funds Performance during Covid-19 - Arifin Hasudungan Manurung; Pardomuan Sihombing (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Investors in Indonesia pay attention to the financial market's investment tools, including mutual funds. Some mutual funds even provide a higher return on investment than alternative stock investments, with a lower level of risk be-cause investment managers properly manage them. This research aims to determine how stock mutual fund success is affected by factors such as stock selection, market timing, mutual fund size, and Covid-19, with Covid-19 serving as a moderator. Purposive sampling was utilized to conduct research on Indonesian equity funds. This study's sample consists of equity funds administered by fourteen investment management firms authorized and regulated by the Financial Services Authority (OJK). Panel data regression analysis in Eviews is used to examine the information. It was discovered that neither mutual fund size nor Covid-19 played a statistically important role in determining the success of equity funds. However, equity fund returns are significantly influenced by company picking and market timing. As a supplementary benefit, Covid-19 can significantly reduce the beneficial effects of overly optimistic stock picking on the returns of equity funds. This research also demonstrates that the effects of mutual fund size and market timing on stock fund returns are not reduced by using Covid-19.